La Relation Entre Le Bilinguisme Precoce Et Les Capacites Cognitives Chez Les Enfants Ages De 5 A 6 Ans - Saliha Bouzid Baa (European Scientific Journal, ESJ, 2016)
The objective of this paper is to present results of a field work in which the aim was to examine the relationship between precocious bilingualism and certain cognitive capacities in 5 and 6 years old children. The cognitive capacities we took into account are attention, visual memory and intelligence. The obtained results permitted to conclude that bilingualism does not constitute an obstacle to the child’s cognitive development on the one hand, and that there is no difference between the bilingual and the monolingual at the advantage of monolinguals on the other hand that lead to the development of certain cognitive capacities namely memory.